Analisis Hubungan Harga Emas, Harga Saham, Nilai Tukar dan Suku Bunga di Indonesia: Pendekatan Vector Error Correction Model (VECM) - Junita Sriwulan; Ariusni Ariusni (Universitas Negeri Padang, 2020)
This studi aim to indentify and analyze the realtionship between Gold Price, Stock Price, Exchange rate and Interest rate in Indonesia. The type of this research is associative descriptive research. Where the data used is monthly data of time series from January 2014 to December 2019 obtained from Bank of Indonesia (BI) and hargaemas.org. Analysis model uses, Vector Error Correction Model (VECM) to see interaction the long and short term between of variabel, Impluse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) in looking at the response of variability to the variables to the variables associated with those shown by other endogenous variables. The finding of this study indicate that:(1) In the short run, Shock of stock price, exchange rate and interest rate do not contribute to the variability of gold price in Indonesia, but shock of exchange rate is only to variability response of gold price on long run. (3) Shock of gold price, exchange rate and interest rate do not contribute to the variability of stock price in short term but variability of stock price is only based on long term gold price shock. (4) Exchange rate variability is contribute by stock price in the short and long term. But, in the long run shock interest rate also to the varibility of stock price. (5) Variability of interest rate is only contibuted by gold price in the short and long term in Indonesia.